Dyscalculia. - Hussain, Khadijah; Soares, Neelkamal (International Journal of Child Health & Human Development, 2022)
Dyscalculia, or math learning disorder, has been defined as current academic skills in math that are well below the average range in culturally and linguistically appropriate tests; cannot be better explained by developmental, neurological, sensory or motor disorders; and significantly interferes with academic achievement, occupational performance, or activities of daily living. Children with dyscalculia can have difficulty learning to count and understanding the one-to-one correspondence between numbers and objects, estimating numbers and quantities, telling time, doing mental math and learning math concepts. Teachers can use screening instruments combined with progress monitoring to identify at-risk students, and diagnostic tools are best administered by special educators or educational psychologists. Between 17% and 70% of children with dyscalculia have dyslexia, and the comorbidity rate of dyscalculia with ADHD is 11%. Preventive programs usually focus on supporting students at risk and assisting them before they fall behind. Remedial interventions involve intensive, multi-component instruction individualized to a child's specific needs, and modifications to instructional practice are suggested for children with dyscalculia. Dyscalculia is a persistent and enduring specific learning disability with life-long impact on an individual's job opportunities and future earning potential. The primary care physician's role in the management of dyscalculia includes ensuring educational advocacy for the family, screening for sensory and medical conditions, initiating appropriate subspecialist referrals and directing families towards community resources.